An experimental and numerical investigation on aerodynamic characteristics for different airfoil sections for external flow - Irsa TALIB (Sukkur IBA Journal of Emerging Technologies)
This research presents the development of a subsonic wind tunnel designed for streamlined airflow, featuring a squared cross-sectional area along its length. The primary focus is on measuring drag and lift on external flow across two different airfoil models. Utilizing a variable-speed centrifugal blower motor in the absence of converging and diverging sections ensures streamlined airflow in the test section. Two airfoil models, NACA-0012 and NACA-2414, fabricated from galvanized iron thin gauge sheet metal, undergo analysis through wind tunnel experiments and numerical simulation. Within the wind tunnel, strain gauge load cells are incorporated to accurately measure drag and lift across the airfoils. Comparative assessments of drag and lift coefficients are conducted at four varying angles of attack (-6.3 degrees to 12.6 degrees) for each airfoil. Results from both wind tunnel experiments and numerical simulations demonstrate precision, closely aligning with literature.